Necesidad de reformar el numeral 3 del art. 110 de la ley reformatoria al código civil; respecto a la causal de divorcio por falta de armonía de las dos voluntades - ROJAS MORA, SANTIAGO RODRIGO (2016)
With the reforms carried out recently by the Civil Code Reform Act published in the Second Supplement to Official Gazette no. 526 of 19 June 2015, divorce became unenforceable by third causal since it has been established that "the normal state disharmony of the two wills in married life. " The assembly has not provided to the possibility of divorce by mutual agreement, as the causal in extipula expressly that there must be disharmony of "two wills"; that is, when one spouse does not want a divorce, the spouse can not sue affected as never show the disharmony of the two wills but only a will of the spouse who does not live in harmony. Then it reads as is the causal, is required to prove the absence of the two wills, which would lead to consensual divorce and not contested divorce, since one of the two spouses must commit acts that demonstrate the lack of harmony for the the other spouse can not live with him, but require disharmony of two wills would be impossible to prove, since the contested divorce arises when one spouse does not want a divorce and when one of them is sued another appears and It is opposed to divorce which in turn indicating the will to stay married, then the judge or the judge may sentence dissolving the marriage because disharmony of the two wills can not show. For these reasons, I propose that paragraph 3 of Art is reformed. 110 of the Civil Code, amended by Law published in Official Gazette no. 526 of 19 June 2015 to allow divorce for the usual state of disharmony one of two wills. In this situation I substantiate my thesis that the Civil Code clarifying on the third grounds for divorce established in our Civil Code and avoiding subjectivity reform.